Corporate Social Responsibility Makin Mesra Program PT. Bank Aceh Syariah Meulaboh Branch - Anisah, Anisah; Harmen, Hamdi; Rusdi, Rusdi; Jalis, Ivon; Mandavairo, Fitria (International Asia Of Law and Money Laundering (IAML), 2024)
This study aims to understand the impact of Corporate Social Responsibility (CSR) Program "MAKIN MESRA" (Poor Community Towards Prosperity) on the welfare of the community in Gampong Lapang, Aceh Barat District. The program is designed to reduce poverty and improve the local economy through the provision of business capital assistance and mentorship. The research employs a qualitative approach with a case study method. Data collection techniques include in-depth interviews with key informants, observations of program implementation, and collection of relevant documents. The research sample includes various key stakeholders, including the regional government represented by the Regional Development Planning Agency (Bappeda) and related agencies, private companies involved in the program, and beneficiary communities in Gampong Lapang. The results indicate that CSR has successfully improved community welfare through the development of small businesses, such as free-range chicken farming. A significant increase in daily income from egg sales has had a direct positive impact on the quality of life of beneficiary families. Additionally, the program has strengthened economic independence and created a domino effect, increasing purchasing power and local economic growth. However, challenges such as business sustainability and adaptation to economic changes still need to be addressed. Closer collaboration between the government, private sector, and the community is crucial to optimizing the effectiveness and impact of the program in the future.